Target protein prediction of Indonesian jamu kunyit asam (Curcumin-tamarind) for dysmenorrhea pain reliever: A network analysis approach - Galuh Wening Permatasari; Mochammad Fitri Atho'illah; Wira Eka Putra (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Background: Dysmenorrhea is a monthly problem for reproductive-age women before or during menstruation. Dynamic changes of prostaglandins (PGs) and progesterone in the late reproduction cycle regulating signal pathways of PGE2 and PGF2 can contribute to menstrual cramps and other dysmenorrhea symptoms. Curcuma longa and Tamarindus indica (CT) are traditional medicines more preferred by Indonesian women to overcome menstrual pain than painkiller drugs.Objective: This study aims to observe potentially active compounds and detailed mechanism of Curcuma longa and Tamarindus indica (CT) as a pain reliever.Methods: Bioactive compounds in the CT were collected from two databases and then screened by bioavailability and drug-likeness parameter by utilizing SwissADME software. The target proteins and genes associated with dysmenorrhea were retrieved from HitPick and GeneCard database. The possibility of how CT healed dysmenorrhea was predicted by protein-protein interaction (PPI) using STRING Webserver and was visualized by Cytoscape v.3.7.0 and REVIGO.Results: Totally, 147 active compounds were obtained from C. longa and 212 active compounds from T. indica. Respectively, 36 and 66 compounds were obtained from C. longa and T. indica by the ADME screening. Finally, 20 and 22 target proteins were identified in both herbs. Then, an overlap analysis of this study showed that four target proteins had strong interaction with pain-related dysmenorrheaConclusion: This study found possible target proteins of the CT to relieve dysmenorrhea. The target proteins included HSD17B1, ALOX5, GSTM1, and ESR2 genes. Further, these findings are needed to be validated by using in vitro and in vivo approaches.